Intuitive decisionmaking: tacit knowing in action by U.S. Armed Forces officers in 2011 - Moilanen, Jon H. (Kansas State University, 2012)
This qualitative inquiry was a naturalistic exploration of participants’ perception or understanding of their intuitive decisionmaking processes. A bounded case study explored how a purposeful sampling of U.S. Armed Forces officers−primarily U.S. Army officers−perceived or understood intuitive decisionmaking in the context of their experiences in contemporary military missions. The purposeful sample was comprised of ten volunteer participants attending their professional Intermediate Level Education (ILE) course in 2011 at the U.S. Army Command and General Staff College. The review of relevant literature used Polanyi's (1958) theory of tacit knowing and personal knowledge [intuition] in making decisions as a philosophical and psychological baseline. U.S. Army doctrine promoted implicit [intuitive] and analytical [deliberate] decisionmaking. Army doctrinal guidance stated that in situations severely constrained in time and requiring an immediate decision, Army leaders rely significantly on intution. A complementary concept advocated creative and critical thinking in order to adaptively solve problems. However, minimal emphasis on intuitive processes and rescinding the term intuitive decisionmaking in Army doctrine indicated a significant gap in Army leader development. This research augmented professional literature on the art and science of military leadership and decisionmaking in the second decade of the 21st century. The exploratory study encouraged further research on how U.S. Armed Forces officers perceive discrete elements or emergent patterns among complex environmental stimuli; understand their tacit knowledge to sense situational cues affecting a problem; and develop their intuitive acumen as a complement to experience and learning toward professional expertise. The participants’ candid insights on their lived and vicarious experiences in intuitive decisionmaking suggested similar leadership value to the adult education community. Other practical benefits included an improved self-efficacy of participants to trust their personal intuition and expertise, and to further explore their tacit knowledge for effective day-to-day living in an ever-changing complex and uncertain world. The experiences of participants indicated the believability of Polanyi’s premise that “we can know more than we can tell.” (Polanyi, 1964, p. x).
Keywords: Intuitive decisionmaking; Intuition; Tacit knowledge; Reflection-in-action; Leadership; Implicit knowledge; Adult Education (0516); Cognitive Psychology (0633); Educational leadership (0449)